Speed and sensitivity of phototransduction in Drosophila depend on degree of saturation of membrane phospholipids - Randall, Alex S.; Liu, Che-Hsiung; Chu, Brian; Zhang, Qifeng; Dongre, Sidharta A.; Juusola, Mikko; Franze, Kristian; Wakelam, Michael J. O.; Hardie, Roger C. (The Journal of Neuroscience, 2015)
Drosophila phototransduction is mediated via a G-protein-coupled PLC cascade. Recent evidence, including the demonstration that light evokes rapid contractions of the photoreceptors, suggested that the light-sensitive channels (TRP and TRPL) may be mechanically gated, together with protons released by PLC-mediated PIP2hydrolysis. If mechanical gating is involved we predicted that the response to light should be influenced by altering the physical properties of the membrane. To achieve this, we used diet to manipulate the degree of saturation of membrane phospholipids. In flies reared on a yeast diet, lacking polyunsaturated fatty acids (PUFAs), mass spectrometry showed that the proportion of polyunsaturated phospholipids was sevenfold reduced (from 38 to ∼5%) but rescued by adding a single species of PUFA (linolenic or linoleic acid) to the diet. Photoreceptors from yeast-reared flies showed a 2- to 3-fold increase in latency and time to peak of the light response, without affecting quantum bump waveform. In the absence of Ca2+ influx or in trp mutants expressing only TRPL channels, sensitivity to light was reduced up to ∼10-fold by the yeast diet, and essentially abolished in hypomorphic G-protein mutants (Gαq). PLC activity appeared little affected by the yeast diet; however, light-induced contractions measured by atomic force microscopy or the activation of ectopic mechanosensitive gramicidin channels were also slowed ∼2-fold. The results are consistent with mechanosensitive gating and provide a striking example of how dietary fatty acids can profoundly influence sensory performance in a classical G-protein-coupled signaling cascade.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Lipidomics; Mechanosensitivity; Phosphoinositide; Phospholipase C; Photoreceptors; PIP2